Otentikasi Dua Faktor Menggunakan Totp dengan SHA-512 untuk Sistem Pemilihan Presiden Mahasiswa - Arisandi, Diki; Hartati, Seri; Vrabora, Givo (Explorer, 2025)
This study originated from the need for a secure election system in academic environments, particularly to address credential theft and cyberattack threats in the security of the Student Presidential election system. Ensuring security in student election systems presents a significant challenge, as conventional authentication methods are prone to voter identity authenticity manipulation. Therefore, this research proposes a two-factor authentication model using Time-Based One-Time Password (TOTP) based on the SHA-512 algorithm. This model provides an additional layer of security through time-based authentication and a stronger hash mechanism against attacks. Testing was conducted involving several user accounts from Gmail applications, where OTP codes were successfully sent to the users' email accounts. The results indicated that TOTP delivery and validation times ranged between 150 and 300 ms, with user satisfaction levels exceeding 80%. The implications of this study include enhanced security in the student presidential election system within academic environments and the potential for broader adoption in other fields requiring user authentication